2008
DOI: 10.1002/anie.200703823
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐Promoted Hydrohydrazination of Terminal Alkynes: An Efficient Domino Synthesis of Indoles

Abstract: Indole click chemistry: The quest for better catalysts for the intermolecular hydrohydrazination to indoles leads to zinc salts. A simple one‐pot synthesis forms indoles from arylhydrazines and terminal alkynes. The pharmacologically relevant indole building blocks are selectively formed in the presence of zinc triflate (Zn(OTf)2) or ZnCl2 (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…Recently, Beller and coworkers reported an excellent method which addresses the above issues. The authors found that the treatment of alkynes with aryl hydrazines 36, in the presence of stoichiometric amounts of Zn(II) salts at 100e120 C in THF, produces substituted indoles 37 in good to high yields (Table 5) [45]. Particularly noteworthy is the fact that eOTBDMS group was well tolerated (Table 5, entry 3).…”
Section: Reactions Triggered By Intermolecular Hydroaminationmentioning
confidence: 95%
“…Recently, Beller and coworkers reported an excellent method which addresses the above issues. The authors found that the treatment of alkynes with aryl hydrazines 36, in the presence of stoichiometric amounts of Zn(II) salts at 100e120 C in THF, produces substituted indoles 37 in good to high yields (Table 5) [45]. Particularly noteworthy is the fact that eOTBDMS group was well tolerated (Table 5, entry 3).…”
Section: Reactions Triggered By Intermolecular Hydroaminationmentioning
confidence: 95%
“…1 Accordingly, many powerful methodologies for the synthesis of these heterocycles have been developed, 2 the majority of these methods involve Fischer-type indole synthesis, 3 reductive cyclization, 4 metal-catalyzed coupling/condensation cascades 5 and electrophilic activation of N -aryl amides. 6 Recently, the utility of enamines in metal catalysis for the formation of valuable indoles has also been reported.…”
mentioning
confidence: 99%
“…has become an important topic because it provides a powerful tool for the synthesis of numerous complex molecules. 9 In this regard, there has been enormous interest in developing sp 3 -C–H bond functionalization, 10 especially those of metal-free couplings. 11 Among the various known synthetic methodologies, the direct formations of C–C and/or C–X bonds from allylic C–H bonds have attracted great attention.…”
mentioning
confidence: 99%
“…The 2,3-disubstitutued indole is assembled through zinc-promoted hydrohydrazination/Fischer indole cascade of protected pentynol 12 . 7 The pyrrolidine 8 is formed through gold(I)-catalyzed cyclization of indole-allene 10 followed by enolate alkylation to install the necessary quarternary center at C-15. Indole-allene substrate 10 is constructed through two sequential alkylation steps: N α -alkylation to introduce the ester, forming 11 , followed by α- N in -indole enolate alkylation to introduce the allene (Fig.…”
Section: Retrosynthetic Strategymentioning
confidence: 99%
“…7 Phenylsulfonamide protection of the N in -position occured cleanly using phenylsulfonyl chloride and potassium hydroxide to yield 9 . Performing a radical bromination/Arbuzov sequence on 2-methyltryptophol 9 afforded phosphonate 7 in 77% yield.…”
Section: Total Synthesis Of Flinderoles B and Cmentioning
confidence: 99%